Native Approaches to Decolonising Education in Institutions of Higher Learning - Walke, Polly (The Australian Journal of Indigenous Education, 2000)
A growing number of Native scholars are involved in decolonising higher education through a range of processes designed to create space for Indigenous realities and Indigenous ways of managing knowledge. Basing their educational approaches on Indigenous ontologies and epistemologies, they are developing Indigenist approaches within higher education. Ward Churchill (1996:509), Cherokee scholar, explains that an Indigenist scholar is one who: Takes the rights of indigenous peoples as the highest priority …who draws on the traditions – the bodies of knowledge and corresponding codes of value – evolved over many thousands of years by native peoples the world over.